Different Effect of Cytrus (Orange) and Lavender Aromatherapy towards Anxiety Level - Arie Jefry Kaarayeno; Rachmat Chusnul Choeron; Maria Irene Ngongo (Journal of Ners and Midwifery, 2022)
Anxiety that occurs continuously, irrationally and increasing in intensity, can interfere with daily activities and become an anxiety disorder. The purpose of the study was to identify differences in the effectiveness of citrus aromatherapy (orange) compared to lavender aromatherapy on anxiety levels in nursing students in dealing with thesis at Tribhuwana Tunggadewi University, Malang. The design of the study used a quasi-experimental design using a two group pre-test-post-test design approach. Respondents in this study were nursing students who were undergoing thesis as many as 66 people, from a population of 83 people with simple random sampling technique. The instrument in this study used experimental intervention. Analysis using Wilcoxon and Mann Whitney test. The result of this analysis was that citrus aromatherapy (orange) with p-value 0.000 and lavender aromatherapy with p-value 0.000, meant that cytus (orange) aromatherapy and lavender aromatherapy both significantly reduce anxiety levels. However, there was a significant difference between citrus aromatherapy (orange) and lavender aromatherapy on the level of anxiety in students who were working on their thesis at Tribhuwana Tunggadewi University, Malang, which was shown with a p-value of 0.000. It is hoped that further researchers can see or measure which is the most effective between citrus aromatherapy (orange) compared to lavender aromatherapy.